MANAGEMENT OF DELIVERY IN PATIENTS WITH OPHTHALMIC DISEASES - Goshevska Dashtevska E; Pandilov S; Trpevska Shekerinov N (Department of Anaesthesia and Reanimation Faculty of Medicine “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2023)
Introduction: Cesarean section is used more and more often and represents a significant public health problem in medicine. Its frequency in some countries is 2-3 times higher than that recommended by the WHO, and ophthalmic diseases are still considered one of the most common non-obstetric indications for performing this procedure. Purpose: With the intention of understanding the correlation between different ophthalmological entities during pregnancy and how much they are a true indication for avoiding spontaneous labor, we have made this literature review. Our goal is to indicate modern insights in the management of childbirth in patients with ophthalmic diseases. Materials and Methods: When preparing this paper, we accessed several medically relevant databases such as: EMBASE, PubMed and GoogleScholar by entering words of interest: pregnancy, childbirth, ophthalmic diseases, myopia, obstetrics, retinal degenerations. We didactically processed the obtained data, in order to present useful conclusions that would find application in daily clinical practice both among ophthalmologists and among gynecologists and obstetricians. Conclusion: The percentage of pregnant women with ophthalmological diseases who attend ophthalmological examinations during pregnancy is still very small. Patients with certain ophthalmological diseases should be evaluated individually, and according to regular ophthalmological examinations (every trimester) during pregnancy, an individualized decision on the method of delivery should be made.